2021
DOI: 10.1038/s42005-021-00576-6
|View full text |Cite
|
Sign up to set email alerts
|

Deconvolution of dissipative pathways for the interpretation of tapping-mode atomic force microscopy from phase-contrast

Abstract: Phase-contrast in tapping-mode atomic force microscopy (TM-AFM) results from dynamic tip-surface interaction losses which allow soft and hard nanoscale features to be distinguished. So far, phase-contrast in TM-AFM has been interpreted using homogeneous Boltzmann-like loss distributions that ignore fluctuations. Here, we revisit the origin of phase-contrast in TM-AFM by considering the role of fluctuation-driven transitions and heterogeneous loss. At ultra-light tapping amplitudes <3 nm, a unique amplitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…This is an amplitude-modulated technique in which the cantilever is driven by a fixed-amplitude sinusoidal signal . Conservative and non-conservative tip–surface interactions cause a phase shift, which reflects local changes in chemical and mechanical properties, allowing the study of polymers, , conjugated materials, , and sol–gel hybrid materials. , …”
Section: Resultsmentioning
confidence: 99%
“…This is an amplitude-modulated technique in which the cantilever is driven by a fixed-amplitude sinusoidal signal . Conservative and non-conservative tip–surface interactions cause a phase shift, which reflects local changes in chemical and mechanical properties, allowing the study of polymers, , conjugated materials, , and sol–gel hybrid materials. , …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is significant to study the factors affecting phase-imaging theoretically and experimentally. [21,[24][25][26][27][28] The dependence of phase contrast on elastic interaction and inelastic interaction in TM-AFM have been investigated. [21] Some results have revealed the relationships between the phase images and the amplitude values of the free oscillation A 0 and the setpoint amplitude A SP .…”
Section: Introductionmentioning
confidence: 99%
“…[21] Some results have revealed the relationships between the phase images and the amplitude values of the free oscillation A 0 and the setpoint amplitude A SP . [24][25][26] Fasolk et al found that the selecting of the appropriate temperature levels for the phase scanning according to the characteristics of the samples can improve the phase contrast results. [27] Furthermore, a large number of studies have shown that energy dissipation is the key factor affecting the phase imaging of TM-AFM.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the TM-AFM is able to calculate the mechanical properties of the sample, and thus characterize the sample. analysis of the soft and hard characteristics of a sample [5].Accurate measurement of the mechanical properties of a sample is an important method for sample characterization; with an accurate mechanical model established and verified, TM-AFM can accurately measure the mechanical properties. In TM-AFM, an oscillating nano-scale cantilevered probe is brought near the surface of a sample; the proximity and oscillation amplitude are adjusted so the probe taps the surface during each cycle; the tapping force is indirectly controlled using as feedback the change in probe amplitude at each tap.…”
mentioning
confidence: 99%
“…In this way, the TM-AFM is able to calculate the mechanical properties of the sample, and thus characterize the sample. analysis of the soft and hard characteristics of a sample [5].…”
mentioning
confidence: 99%